MANIFESTATION OF NATIONAL CULTURAL STEREOTYPES IN THE ACT OF SPEECH - Abduqodirova Madina Abduqayum qizi (TADQIQOTLAR, 2025)
Annotation. This article analyzes the manifestation of national cultural stereotypes in the act of speech. It explores how cultural and national stereotypes are formed, spread, and affect social relations through speech acts. From a linguistic perspective, the article also examines the peculiarities of the speech act of reproach and how national and cultural identities are expressed through it.